The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0104-77602011000300010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal treatment on the physicochemical characteristics of giant bamboo

Abstract: Despite countless use possibilities for bamboo, this material has two major disadvantages. One drawback is the low natural durability of most bamboo species due to presence of starch in their parenchyma cells. The other equally important drawback is the tendency bamboo has to present dimensional variations if subjected to environmental change conditions. In an attempt to minimize these inconveniences, strips (laths) of Dendrocalamus giganteus Munro were taken from different portions of the culm and subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The effects of treatment appear to vary by species. Colla et al [11] explored the impact of heat treatment on Dendrocalamus giganteus Munro, also known as giant bamboo. The authors found that thermal treatment increased the dynamic modulus and modulus of rupture up to 140°C, with additional increase in temperatures resulting in decreased strength and degradation at a micro-scale level.…”
Section: Processing Effects In Bamboomentioning
confidence: 99%
“…The effects of treatment appear to vary by species. Colla et al [11] explored the impact of heat treatment on Dendrocalamus giganteus Munro, also known as giant bamboo. The authors found that thermal treatment increased the dynamic modulus and modulus of rupture up to 140°C, with additional increase in temperatures resulting in decreased strength and degradation at a micro-scale level.…”
Section: Processing Effects In Bamboomentioning
confidence: 99%
“…The effect of thermal treatment on Dendrocalamus giganteus bamboo properties was studied [14]. It was encountered that ultrasound velocity (V LL ) was consistently improved (≈ 32 % -38 %) after the treatment up to 260 ºC.…”
Section: Resultsmentioning
confidence: 99%
“…The same method was recently employed to determine dynamic modulus of elasticity of eucalypt treated wood [13]. In another work, it was observed that ultrasound wave velocity was significantly improved in thermally treated bamboo [14].…”
Section: Introduction *mentioning
confidence: 99%
“…Many bamboo species have been investigated for their mechanical behavior after thermal modification. Investigations were done for commercial species from Vietnam (Nguyen et al 2012), Ethiopia (Starke et al 2016), Brazil (Colla et al 2011), China (Zhang 2013), andColombia (Archila et al 2014). Colla et al (2011) treated Asian Dendrocalamus giganteus in inert and non-inert atmospheres for several hours, resulting in improved thickness swelling and stable mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations were done for commercial species from Vietnam (Nguyen et al 2012), Ethiopia (Starke et al 2016), Brazil (Colla et al 2011), China (Zhang 2013), andColombia (Archila et al 2014). Colla et al (2011) treated Asian Dendrocalamus giganteus in inert and non-inert atmospheres for several hours, resulting in improved thickness swelling and stable mechanical properties. Yun et al (2016) investigated Chinese moso Phyllostachys pubescens bamboo and explained the mechanical weakness with changes in crystallinity of bamboo cellulose.…”
Section: Introductionmentioning
confidence: 99%